Sialocele in the cat. A report of 2 cases - TSIOLI (Β. ΤΣΙΩΛΗ) V.; BRELLOU (Γ. ΜΠΡΕΛΛΟΥ) G.; SIZIOPKOU (Χ. ΣΙΖΙΟΠΚΟΥ) C.; VAMVAKEROU (Μ. ΒΑΜΒΑΚΕΡΟΥ) M.; GEORGAKI (Β. ΓΕΩΡΓΑΚΗ) V.; VOUTSINOU (Α. ΒΟΥΤΣΙΝΟΥ) A.; MASTORA (Χ. ΜΑΣΤΟΡΑ) C.; PAPAZOGLOU (Λ.Γ. ΠΑΠΑΖΟΓΛΟΥ) L. G. (Journal of the Hellenic Veterinary Medical Society, 2018)
In the present article the history, physical examination findings, laboratory test results, treatment, follow up and outcome of 2 cats with sialoceles were reported. Both cats were presented with a painless fluctuant cervical swelling. In one cat a ranula was also present. Aspiration of the swellings detected highly viscous fluid and cytology of the aspirates was consistent with the appearance of saliva. A diagnosis of sialocele was made. Both cats were managed by resection of the mandibular and sublingual gland complex through a lateral approach. In case 2 marsupialization of the ranula was also performed. The histopathological examination of the excised tissues in one cat was compatible with chronic inflammation of the mandibular and sublingual gland. The outcome was favorable in both cases and no relapses were detected after a mean follow up time of 13 months.